FORENSIC AND LANGUAGE LABORATORY AS ONE OF THE MAIN SUPPORT TO PRODUCE PROFESSIONAL HUMAN RESOURCES IN IMMIGRATION TECHNOLOGY MANAGEMENT PROGRAM AT IMMIGRATION POLYTECHNIC - Isidorus Anung Prabadhi; Reno Mareno Sidik (Jurnal Ilmiah Kajian Keimigrasian, 2021)
Immigration as the gatekeeper of the country is required to have human resources (HR) who have competence in the immigration field and have a thorough understanding of immigration technical matters. To achieve this optimally, several improvements are needed that must be made at the TPI Forensic Laboratory, Services at the Immigration Office and in the Language Laboratory as a means of support for students, in this case Taruna is proficient in foreign languages ​​other than Indonesian because later in the field will be directly dealing with various kinds of people. foreigners who come to Indonesia. This is related to the real situation in the field which shows that the Lab. Forensics for TPI has not yet reached an ideal state, which should be updated regularly according to their needs and demands. Apart from PCs and similar facilities, good electricity and good network is also something that is no less important. All of this with the main objective, namely, efforts to improve the quality of human resources and create ideal conditions with the supporting facilities for the learning of cadets, namely, the Forensic Laboratory for TPI and the Language Laboratory at the Immigration Polytechnic.